Mobile learning student worksheet based on socio-scientific-issues: Enhancing students’ scientific literacy skills in biology - Aga Arizen; S. Suhartini (University of Muhammadiyah Malang, 2020)
The 21st-century science and technology rapid development requires suitable educational tools to meet the expected learning outcomes desired. This study aimed at producing a mobile learning student worksheet based on Socio-Scientific-Issues (SSI) which is feasible to use in biology teaching activity as well as finding out its effectiveness in enhancing students' scientific literacy skills. This study research and development (R&D) used the ADDIE model. The effectiveness test of mobile learning student worksheet in enhancing students’ scientific literacy skills was done by using a one-group pretest-posttest design. The research findings indicated that the developed mobile learning student worksheet based on SSI is feasible to use in biology teaching activity and become the considerable tool in enhancing students’ scientific literacy skills based on the n-gain score of 0.75 (high category). Thus, it is suggested for science teachers, particularly biology teachers, to adopt this tool to support the learning activity they conduct.